SURVEI PEMBINAAN PRESTASI CABANG OLAHRAGA BOLA TANGAN DI KOTA SEMARANG TAHUN 2023 - Maya Putri Valentina; Setya Rahayu (UNIVERSITAS TUNAS PEMBANGUNAN SURAKARTA, 2025)
Achieving achievement requires structured, sustainable, and continuous coaching. The purpose of this study was to determine the coaching of handball sports achievements in Semarang City. The research method uses a descriptive qualitative approach, data collection techniques using observation, interviews and documentation. The instruments in this study include achievement coaching stages, training programs, funding, and facilities and infrastructure. The data sources in the study were administrators, coaches, athletes, research sites, and documents. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the study found that 1) The achievement coaching stage consists of a massaging stage carried out through competitions held by ABTI Semarang City, the nursery stage is carried out by selecting and monitoring prospective athletes through competitions that are held, then selected again for achievement coaching to become ABTI Semarang City fostered athletes, the achievement coaching stage is carried out by selecting core athletes to achieve championship targets, as evidenced by the achievement of the achievements of ABTI Semarang City athletes is good. 2) The training program is included in the good category, the program is arranged periodically (training periodization), 3) Funding obtained annually from KONI Semarang City, 4) Facilities and infrastructure are quite good but the size of the field used is still not in accordance with the standards. The conclusion of the development of handball sports achievements in Semarang City seen from the aspects of the stages of massaging, breeding, achievement, training programs, funding, and facilities and infrastructure is good.